Diagnostic Concordance Characteristics of Oral Cavity Lesions - Ufuk Tatli; Özgür Erdoğan; Aysun Uğuz; Yakup Üstün; Yaşar Sertdemır; İbrahim Damlar (The Scientific World Journal)
Purpose. The objective of this study was to evaluate the diagnostic concordance characteristics of oral cavity lesions by comparing the clinical diagnosis of the lesions with the histopathologic diagnosis. Material and Method. A retrospective analysis was conducted on the patients, who were admitted with oral cavity pathology and underwent biopsy procedure between 2007 and 2011. The oral cavity lesions were classified into 6 different groups as odontogenic cysts, nonodontogenic cysts, odontogenic tumors, nonodontogenic tumors, malignant tumors, and precancerous lesions in accordance with the 2005 WHO classification. The diagnoses were also recategorized into 3 groups expressing prognostic implications as benign, precancerous, and malignant. The initial clinical diagnoses were compared with the histopathologic diagnoses. Data were analyzed statistically. Results. A total of 2718 cases were included. Histopathologic diagnosis did not match the clinical diagnosis in 6.7% of the cases. Nonodontogenic tumors and malignant tumors had the highest misdiagnosis rates (11.5% and 9%, resp.), followed by odontogenic tumors (7.7%), precancerous lesions (6.9%), and odontogenic cysts (4.4%). Clinicians were excelled in diagnosis of benign and precancerous lesions in clinical setting. Conclusion. The detailed discordance characteristics for each specific lesion should be considered during oral pathology practice to provide early detection without delay.